SAR Image Simulation in the Time Domain for Moving Ocean Surfaces - Yoshida, Takero (Molecular Diversity Preservation International (MDPI), 2013)
This paper presents a fundamental simulation method to generate synthetic aperture radar (SAR) images for moving ocean surfaces. We have designed the simulation based on motion induced modulations and Bragg scattering, which are important features of ocean SAR images. The time domain simulation is able to obtain time series of microwave backscattering modulated by the orbital motions of ocean waves. Physical optics approximation is applied to calculate microwave backscattering. The computational grids are smaller than transmit microwave to demonstrate accurate interaction between electromagnetic waves and ocean surface waves. In this paper, as foundations for SAR image simulation of moving ocean surfaces, the simulation is carried out for some targets and ocean waves. The SAR images of stationary and moving targets are simulated to confirm SAR signal processing and motion induced modulation. Furthermore, the azimuth signals from the regular wave traveling to the azimuth direction also show the azimuthal shifts due to the orbital motions. In addition, incident angle dependence is simulated for irregular wind waves to compare with Bragg scattering theory. The simulation results are in good agreement with the theory. These results show that the simulation is applicable for generating numerical SAR images of moving ocean surfaces.